EGFRvIII mutations can emerge as late and heterogenous events in glioblastoma development and promote angiogenesis through Src activation - Eskilsson, Eskil; Rosland, Gro V.; Talasila, Krishna M.; Knappskog, Stian; Keunen, Olivier; Sottoriva, Andrea; Foerster, Sarah; Solecki, Gergely; Taxt, Torfinn; Jirik, Radovan; Fritah, Sabrina; Harter, Patrick N.; et al. (Neuro-Oncology, 2016)
AbstractBackground. Amplification of the epidermal growth factor receptor (EGFR) and its mutant EGFRvIII - are among the most common genetic alterati